Could stool collection devices help increase uptake in bowel cancer screening programmes?. (December 2018) - Morling, JR; Barke, AN; Chapman, CJ; Logan, RF
Objective: To understand the usage and acceptability of a faecal collection device amongst participants in the National Health Service Bowel Cancer Screening Programme, with the aim of influencing future uptake. Setting: Participants completing faecal occult blood test retests as part of the routine Bowel Cancer Screening Programme in Eastern England. Methods: A faecal collection device and questionnaire were sent to all potential retest participants during a one-month period to collect information on prior stool collection methods and ease of use and usefulness of the enclosed faecal collection device. Results: Out of 1087 participants invited, 679 (62.5%) returned their questionnaire. Of these, 429 (63.2%) trialled the faecal collection device at least once, 163 (38.4%) found the device made collecting their sample easier than previously, 189 (44.6%) found it made collection more difficult and 72 (17.0%) said it made no difference. Similar numbers reported finding that the faecal collection device made collecting the sample more pleasant (130, 31.5%), less pleasant (103, 25.0%) and no different (179, 43.4%) compared with previous collection without a faecal collection device. Conclusion: Although a small proportion of participants found the faecal collection device helpful, a considerable majority did not or did not use it at all. Offering faecal collection devices is unlikely to produce a substantial increase in bowel cancer screening uptake.